About the Kerr Nature of the Stellar-mass Black Hole in GRS 1915+105 - Zhang, Yuexin; Abdikamalov, Askar B.; Ayzenberg, Dimitry; Bambi, Cosimo; Dauser, Thomas; Garcia, Javier; Nampalliwar, Sourabh (Astrophysical Journal, 2019)
We employ the accretion disk reflection model RELXILL_NK to test the spacetime geometry around the stellar-mass black hole in GRS 1915+105. We adopt the Johannsen metric with the deformation parameters alpha(13) and alpha(22), for which the Kerr solution is recovered when alpha(13) = alpha(22) = 0. We analyze a NuSTAR observation of 2012, obtaining vanishing and non-vanishing values of the deformation parameters depending on the astrophysical model adopted. Similar difficulties were not found in our previous tests with other sources. The results of this work can shed light on the choice of sources suitable for testing the Kerr metric using X-ray reflection spectroscopy and on the parts of our reflection models that more urgently require improvement.
CRIS-Team WoS Importer:2019-04-25